Community Service Focused on Food of Animal Products in Nagari Saniangbaka, X Koto Singkarak, Regency of Solok, West Sumatra - Aronal Arief Putra; Afriani Sandra; Deni Novia; Riri Permata Sari; Andini Valentina Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Community service in Nagari Saniangbaka, X Koto Singkarak, Kabupaten Solok was conducted. This project was divided into three activities, i.e., extension of healthy and nutritious foods; extension of safe, healthy, authentic, and halal foods; and training of salted egg manufacturing. Students of SD Negeri 20 Saniangbaka, MTs Muhammadiyah Saniangbaka, and women of the Sumpadang clan were chosen to participate in these three activities, respectively. For the first and the second activities, the students were involved in a short talk, discussion, quiz, and distribution of UHT milk. For the third activity, the women were trained to make salted eggs by applying two processing methods, i.e., coating paste and immersion in brine solution. In general, those activities were run well with positive participant responses. The two former activities could improve the knowledge and awareness of the students in choosing and consuming the food. At the same time, the latter activity furnishes women with the ability to make various egg products for family consumption. Also, it prepares the essential knowledge that could be developed into an entrepreneurship option.